2010
DOI: 10.1115/1.3213555
|View full text |Cite
|
Sign up to set email alerts
|

Adiabatic and Overall Effectiveness Measurements of an Effusion Cooling Array for Turbine Endwall Application

Abstract: An experimental analysis for the evaluation of adiabatic and overall effectiveness of an effusion cooling geometry is presented in this paper. Chosen configuration is a flat plate with 98 holes, with a feasible arrangement for a turbine endwall. Fifteen staggered rows with equal spanwise and streamwise pitches (Sx/D=Sy/D=8.0), a length to diameter ratio of 42.9 and an injection angle of 30 deg are investigated. Measurements have been done on two different test samples made both of plastic material and stainles… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(8 citation statements)
references
References 26 publications
1
7
0
Order By: Relevance
“…Because there was no coolant attached to the surface, the improved cooling effectiveness for the outward and inward cases compared to the closed case must have come from in-hole convection. Similar to the current study, Facchini et al [2] found that when there were conduction effects, effusion holes acted as a heat sink due to the in-hole convection, especially at higher blowing ratios.…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…Because there was no coolant attached to the surface, the improved cooling effectiveness for the outward and inward cases compared to the closed case must have come from in-hole convection. Similar to the current study, Facchini et al [2] found that when there were conduction effects, effusion holes acted as a heat sink due to the in-hole convection, especially at higher blowing ratios.…”
Section: Resultssupporting
confidence: 88%
“…In addition, they found that the momentum flux ratio for the effusion jets did not have any impact on the effectiveness for the first three rows of holes. In a different study with only effusion cooling, Facchini et al [2] found that increasing the effusion blowing ratio generally led to decreased adiabatic effectiveness due to jet separation; however, overall effectiveness increased at high blowing ratios due to in-hole convection. Martin and Thorpe [3] studied the effects of freestream turbulence intensity on effusion cooling without dilution jets and found that at low blowing ratios of the effusion jets (M eff,in < 0.5), high freestream turbulence resulted in decreased adiabatic effectiveness; whereas at relatively high blowing ratios, up to M eff,in ¼ 1.4, high freestream turbulence caused an increase in adiabatic effectiveness.…”
Section: Relevant Past Studiesmentioning
confidence: 99%
“…4.4. The thermal analysis of such a system can be performed using different methods, e.g., full CFD analysis of the cooling air and the mainstream [3,4], a decoupled conjugate approach (using CFD for the internal cooling and empirical correlation to model the mainstream) [2], or using suitable empirical correlations [5,6]. The outcome of the thermal analysis, using these methods, is the temperature and heat transfer coefficients on the external surface of the outer skin and the internal walls for a given Reynolds number at the impingement holes and mainstream temperature and velocity.…”
Section: The Problem Statementmentioning
confidence: 99%
“…( 16) and (18), i.e., Tf f f , and the heat flux to the inner wall is taken to be zero. Several analyses were then performed for different values of the wavelength in the range λ f /L ∈ 10 −1 -10 1 and H/t ∈ [3][4][5][6][7][8][9][10].…”
Section: 3mentioning
confidence: 99%
“…Experiments to determine adiabatic coolant-film effectiveness (ACE) generally involve measuring spatially resolved surface temperature distributions using techniques such as thermochromic liquid crystal [1,2] and infra-red (IR) Thermography [3,4]. The measurement surface is usually manufactured from a material with an extremely low thermal conductivity in order to satisfy the adiabatic condition.…”
Section: Introductionmentioning
confidence: 99%